The Role of Basic Psychological Needs in Well-Being During the COVID-19 Outbreak: A Self-Determination Theory Perspective - Šakan, Dušana; Žuljević, Dragan; Rokvić, Nikola (Frontiers in Public Health, 2020)
Due to the Coronavirus outbreak, people around the world are facing various challenges in maintaining their well-being, which can be compromised due to risk of illness and harsh measures of social distancing. As proposed by the Self-Determination Theory, basic psychological needs are essential nutrients of well-being. The aim of this study was to examine the role of basic psychological needs in well-being during the pandemic. A sequential mediation model was examined, that links positive and negative affectivity to well-being (satisfaction with life and general distress) through satisfaction and frustration of the basic psychological needs (for autonomy, competence and relatedness). The study involved 965 participants (Mage=29; 57% females) from Serbia. The Basic Psychological Needs Satisfaction and Frustration scale, Satisfaction with Life Scale, Depression Anxiety Stress Scale 21 and The Serbian Inventory of Affect based on the Panas-X were used. All the tested models were statistically significant. Controlling for age, gender, having children, health, employment and marital status, direct effects in all models were highly significant, explaining up to 59% of criteria variance. The proportion of the explained variance was even higher when accounting for indirect effects. Sequential mediation models revealed that the indirect relationships between positive and negative affectivity and satisfaction with life and general distress were serially mediated by Autonomy satisfaction, Competence Frustration, Relatedness Satisfaction and Relatedness Frustration. This study raised an important question on how the disposition to experience more positive or negative emotions affects the change in subjective well-being. These results, coherent with the Self-Determination Theory postulates, add to the understanding of human functioning in the times of extraordinary circumstances during a pandemic, by suggesting that satisfaction and frustration of basic psychological needs might have a key role in obtaining optimal well-being.